1990
DOI: 10.1143/jjap.29.l804
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Caused by Structural Changes in Amorphous Ni-P Alloy

Abstract: We present measurements of the electrical resistivity ρ(T ) on high-quality single-crystalline CeNiSn under both hydrostatic pressure up to 1 GPa and uniaxial pressure up to 0.25 GPa. At ambient pressure, ρ(T ) along the orthorhombic a-axis (b-axis) shows two maxima at T L = 12 K (14 K) and T H = 74 K (40 K), respectively, which arise from the Kondo scattering of conduction electrons by the crystal-field ground state and excited states. With increasing hydrostatic pressure, both T L and T H increase linearly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…That is, they are produced by the atomic motions on the scale of the unit cell (-lo-'' m) as lizardite transforms to a glass. Notably, acoustic emissions are also observed upon recrystallization of glasses (that is, the reverse of our experiments); however, the origin of these events is not well understood (31).…”
Section: Implications For Deep Earthquakes and Recycling Of Water Intsupporting
confidence: 48%
“…That is, they are produced by the atomic motions on the scale of the unit cell (-lo-'' m) as lizardite transforms to a glass. Notably, acoustic emissions are also observed upon recrystallization of glasses (that is, the reverse of our experiments); however, the origin of these events is not well understood (31).…”
Section: Implications For Deep Earthquakes and Recycling Of Water Intsupporting
confidence: 48%
“…In this manner, area ratios of the amorphous portion and three types of crystalline patterns of the sample film heated at various temperatures were measured. The thickness of the sample film was significantly smaller than the size of each crystalline pattern and the change in density caused by crystallization of the sample film was so small as to be negligible (11 ). Therefore, the existence ratio of the respective crystalline patterns in the sample film can be represented by their area ratio measured.…”
Section: Resultsmentioning
confidence: 99%
“…On the deposit reaction of electro-or electroless deposited amorphous Ni-P alloy (hereafter referred to as a-Ni-P) and the properties of deposited film caused by deposit conditions, a number of studies have been reported (5-8). Studies have been performed also on the transformation of a-Ni-P by heating and a change in properties accompanying the transformation, using such methods as x-ray diffraction, electron diffraction, thermal analyses including differential scanning calorimetry (DSC) and others (5,6,(9)(10)(11).The results of these studies show that a-Ni-P crystallizes by heating and various Ni=Py crystals (x and y represent atomic composition ratio) and Ni grow (5,6,9,12).Nevertheless, there has been no report on quantitative measurements of the existence ratios of the crystals in the process of electrodeposited a-Ni-P transformation by heattreatment at a constant rate of heating, as functions of temperature. We heated electrodeposited a-Ni-P sample films to various temperatures at a constant rate of heating, etched them, and observed with an optical microscope three kinds of characteristic crystalline patterns which grew or disappeared as the temperature changed.…”
mentioning
confidence: 99%
See 1 more Smart Citation